Proton MR Spectroscopy Correlates of Frontal Lobe Function in Healthy Children - Ozturk, A.; Degaonkar, M.; Matson, M.A.; Wells, C.T.; Mahone, E.M.; Horská, A. (American Journal of Neuroradiology, 2009)
BACKGROUND AND PURPOSE: Neuroimaging methods have been used to improve our understanding of the topographic organization of the brain. In our study, proton 1H-MR spectroscopic imaging was used to evaluate frontal lobe function. The goal was to determine the relationship between neuropsychological measures of frontal lobe function and levels of a surrogate neuronal marker, N-acetylaspartate (NAA), in typically developing healthy children and adolescents.MATERIALS AND METHODS: Fifty-one healthy children (25 girls; 6.2–18.3 years of age; mean age, 12.3 ± 3.6 years) were examined. All children completed a neuropsychological assessment including measures of attention, executive function, memory, language, and visual and motor skills. 1H-MR spectroscopic imaging was performed by using a multisection spin-echo sequence at 1.5T. General linear model analysis of covariance was used to examine the relationship between the neuropsychological test scores and NAA/creatine (Cr) ratios, controlling for age and sex.RESULTS: A positive relationship between frontal lobe white matter NAA/Cr ratio and performance on 2 neuropsychological tests associated with frontal lobe function was detected. The Purdue Pegboard right-hand scores were higher with increasing NAA/Cr in the left frontal white matter (P = .047), and Stanford-Binet-IV “Bead Memory” scores improved with increasing NAA/Cr ratio in the right frontal white matter (P = .032).CONCLUSIONS: An association between frontal white matter NAA/Cr ratios and 1) measures of manual speed and dexterity, and 2) visual working memory was detected. Our data may provide a quantitative basis for assessment of frontal lobe impairments in disease states.